The Jewelry Design from Natural Environment Based On Tropical Nature Of Indonesia - Angelina, Donna (Idealogy Journal, 2020)
Nature can influence people for some aspects. Most of art fields are inspired by nature. Nature can demonstrate visual composition that is accepted to have value aesthetical and can deliver an emotional feeling to the viewer. That is the reason why artists express the beauty of nature in their works as aesthetic reaction or through appreciation process towards nature. I believe that every experience from each individual with nature can influence their life. The result from the interaction is reflected into one's social and cultural life and it becomes symbols used as philosophy of one's life. So, in my works, with object boundaries of the tropical nature of Indonesia, I try to express how nature affects the human life in modern jewelry.